The Effect of Cooking Class on the Cognitive Abilities of Group a Kindergarten Children in Cluster IV Gedangan Sidoarjo District - Adhimah, Syifaul; Bachri, Bachtiar Syaiful; Jannah, Miftakhul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to determine the effect of cooking class activities on the cognitive abilities of group A children in Cluster IV, Gedangan Sidoarjo District. This study uses a quasi-experimental design through a quantitative approach. The experimental design used was nonequivalent control group design. The subjects in this study were the children of group A RA Al Islah Karangbong with a total of 51 children as the experimental group and PAUD Tashwirul Afkar Karangbong with a total of 30 children as the control group. Data analysis techniques in this study used non-parametric statistics with the Mann Whitney Test. The results of this study indicate that "there is an effect of cooking class activities on the cognitive abilities of Group A kindergarten children in Cluster IV Gedangan Sidoarjo District" with a statistical value of Z = -4.076 with a significance level of 0.000 or less than 5%. This shows that there is an effect of cooking class activities on the cognitive abilities of Group A kindergarten children. Cooking class activities can be used as an interesting and fun learning reference for children in improving children’s cognitive abilities because children get direct experience.